Blame it on anesthesia: A clinical case of postpartum complication after the intervention of anesthesiology for labor analgesia - Samuel Ramos; Paulo Muchacho; Hélder Cavaco; Célia Xavier (Wolters Kluwer Medknow Publications, 2016)
Anesthesiologists are often prevented from performing a follow-up of clinical cases due to the specific characteristics of their activity and may be blamed for complications not directly related to their interventions. Moreover, prudent strategies for communicating the diagnostic hypotheses are not always used, with relevant repercussions on the responsibilities imputed. Acute urinary retention (AUR) in pregnant women is a known complication of the postpartum period. Studies have reported the association between symptomatic AUR and neuraxial anesthesia/analgesia, instrumental labor, nulliparity, and episiotomy and have stated them to be the main risk factors of AUR. Severe neurological lesions resulting from the neuraxial approach, which is the main anesthesiologist intervention, is rare (0.0012-0.004%). In this study, we describe a case of a nulliparous pregnant admitted to the Obstetrics Department who developed AUR. We suggest that there must be a cautious attitude in the practice of medicine when allocating responsibilities, particularly in clinical syndromes that are not yet well-explained.